Time changes with the embodiment of another's body posture. - Francisco C Nather (Public Library of Science (PLoS), 2011)
The aim of the present study was to investigate whether the perception of presentation durations of pictures of different body postures was distorted as function of the embodied movement that originally produced these postures. Participants were presented with two pictures, one with a low-arousal body posture judged to require no movement and the other with a high-arousal body posture judged to require considerable movement. In a temporal bisection task with two ranges of standard durations (0.4/1.6 s and 2/8 s), the participants had to judge whether the presentation duration of each of the pictures was more similar to the short or to the long standard duration. The results showed that the duration was judged longer for the posture requiring more movement than for the posture requiring less movement. However the magnitude of this overestimation was relatively greater for the range of short durations than for that of longer durations. Further analyses suggest that this lengthening effect was mediated by an arousal effect of limited duration on the speed of the internal clock system.